2021
DOI: 10.1590/s1808-185120212004250308
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the Goutallier Classification System in the Evaluation of the Multifidus Muscle

Abstract: Introduction: The paravertebral musculature is essential for the biomechanics and stability of the spine, and its involvement in the pathophysiology of spinal diseases has been demonstrated. Qualitative evaluation of muscle degeneration is usually performed by analyzing the fat infiltration rate proposed by the Goutallier classification system. Objective: The objective of this study is to analyze the intra- and interobserver agreement of the Goutallier Classification for the evaluation of fatty degeneration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…Fatty infiltration of the multifidus muscles was evaluated according to the Goutallier classification. A reliability study conducted by Soares RO, et all (2021) found that the Goutallier Classification System showed moderate interobserver and almost perfect intraobserver agreement in the evaluation of the fat infiltration rate of the multifidus muscle (15).…”
Section: Multifidus Musclesmentioning
confidence: 99%
“…Fatty infiltration of the multifidus muscles was evaluated according to the Goutallier classification. A reliability study conducted by Soares RO, et all (2021) found that the Goutallier Classification System showed moderate interobserver and almost perfect intraobserver agreement in the evaluation of the fat infiltration rate of the multifidus muscle (15).…”
Section: Multifidus Musclesmentioning
confidence: 99%